Pengaruh Direct Marketing dan Responsiveness Terhadap Keputusan Pembelian Produk Tabungan Emas pada PT. Pegadaian cabang Cilamaya (Peneliti.net, 2022)
This study aims to determine the effect of Direct Marketing and Responsiveness on Purchase Decisions. The method used is a quantitative research method with descriptive and verification analysis. The population in this study amounted to 154 people. The sampling technique is using non-probability techniques with incidental sampling techniques. The data analysis technique used is path analysis. Based on the descriptive analysis in this study, it shows that Direct Marketing has an average score of 634.5 which means that the level of direct marketing is good, Responsiveness gets an average score of 586.8, which means that the level of responsiveness is good, and Purchase Decisions get an average score of - an average of 571.3 means that the level of purchasing decisions is good. Based on the results of the verification analysis shows the value of the correlation coefficient between Direct Marketing and Responsiveness variables obtained a value of 0.698 which means it has a strong, positive and significant correlation level. Partial Influence of Direct Marketing on Purchase Decisions of 43.0%. The influence of Partial Responsiveness on Purchase Decisions 33.7%, it can be stated that Direct Marketing has a greater influence on Purchase Decisions than Responsiveness. The simultaneous influence of Direct Marketing and Responsiveness on Purchase Decisions is 76.7% while the remaining 23.3% is the influence of other variables not examined.